2021
DOI: 10.1007/s40808-021-01172-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 outbreak on tropospheric NO2 pollution assessed using Satellite-ground perspectives observations in India

Abstract: The global outbreak of Novel Corona Virus 2019 (SARS-CoV-2) has made worldwide lockdown including India since March 24, 2020. The current research aims at the improvements of nitrogen dioxide (NO 2 ) during the COVID-19 lockdown in India. This research has been done using both the open source data sets taken from satellite and ground based for better analysis. For the satellite-based analysis, the Sentinel 5 Precauser’s Tropospheric NO 2 from the European Space Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similarly, with the COVID-19 precautions, compared to the same days of 2019, the decrease rate in NO2 concentrations in some countries, regions, and cities after the lockdown is 30% for Wuhan, 25% for China, Europe, Italy, France, Spain, 30% for the USA, 40% for Mumbai, 50% for New Delhi (Muhammad et al, 2020), and 54.3% São Paulo state, Brazil (Nakada & Urban, 2020). According to data from Sentinel-5P Nitrogen Dioxide tropospheric column, NO2 concentration decreased by 40-50% from 2019 January to 2020 April in industrial areas in India (Balamadeswaran et al, 2021;ESA, 2021b). In a study conducted in the UK, it was stated that the NO2 pollution on the roadsides decreased slightly with the COVID-19 precautions by comparing the same months of 2019 and 2020 (EEA, 2021; ESA, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, with the COVID-19 precautions, compared to the same days of 2019, the decrease rate in NO2 concentrations in some countries, regions, and cities after the lockdown is 30% for Wuhan, 25% for China, Europe, Italy, France, Spain, 30% for the USA, 40% for Mumbai, 50% for New Delhi (Muhammad et al, 2020), and 54.3% São Paulo state, Brazil (Nakada & Urban, 2020). According to data from Sentinel-5P Nitrogen Dioxide tropospheric column, NO2 concentration decreased by 40-50% from 2019 January to 2020 April in industrial areas in India (Balamadeswaran et al, 2021;ESA, 2021b). In a study conducted in the UK, it was stated that the NO2 pollution on the roadsides decreased slightly with the COVID-19 precautions by comparing the same months of 2019 and 2020 (EEA, 2021; ESA, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The mean annual temperature is >24 °C in tropical regions, 17–24 °C in the subtropical region, 7–17 °C in the temperate region and <7 °C in the Alpine region. India has around 17.5% of the global population and the seventh-largest land region 26 of 3 287 263 km 2 . Here, we analyse NO 2 column density over rural regions of India.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] By 2030, India's coalbased power production is expected to be more than double than that of the current 197 GW, which is predicted to inict 186 500-229 500 deaths per year. 26,27 Estimates of India's annual premature mortality due to poor air quality range from 580 000 to more than one million individuals. 28 Karambelas et al 29 studied the premature mortality in rural regions (3 83 600) due to PM 2.5 , which proves to be a notable monetary loss to the Indian economy.…”
Section: Introductionmentioning
confidence: 99%
“…Climate scientists revealed that the level of GHGs in the atmosphere was dropped to the lowest ever since World War II (Nigam et al, 2021). Balamadeswaran et al (Balamadeswaran et al, 2021) found that NO 2 in the atmosphere fell significantly during the lockdown. Few vehicles were running on the roads, and closed down industries.…”
Section: Air Pollutionmentioning
confidence: 99%